2022
DOI: 10.1021/acs.inorgchem.2c00360
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrolysis of Thiolates to Alcohols

Abstract: A new and efficient catalytic hydrolysis of aliphatic and aromatic thiolates under ambient conditions is presented. Previously, we have demonstrated (Ganguly et al., Inorg. Chem. 2018, 57, 11306–11309) the Co­(II) mediated stoichiometric hydrolysis of thiols to produce alcohols/phenols along with a binuclear dicobalt­(II)-hydrosulfide complex, [Co2(PhBIMP)­(μ2-SH)­(DMF)]2+ (1) (PhBIMP is the anion of 2,6 bis­[(bis­((N-1-methyl-4,5- diphenylimidazoylmethyl) amino)­methyl]- 4-methylphenol). In the present work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 64 publications
9
19
0
Order By: Relevance
“…Moreover, Zn­(II) could not mediate the C–S bond cleavage of thiolates in yet another binucleating ligand system, N -Et-HPTB 1– ( N -Et-HPTB 1– is the deprotonated version of N , N , N ′, N ′-tetrakis­[2-(1- ethylbenzimidazolyl)]-2-hydroxy-1,3-diaminopropane) , in one of our previous studies, although Fe­(II) and Co­(II) could mediate the hydrolysis reaction , using the same N -Et-HPTB 1– ligand. Therefore, it becomes quite apparent that Zn­(II) is indeed comparatively much less efficient in mediating the C–S bond cleavage of thiolates, and hence even with the use of the PhBIMP 1– ligand, which, by far, has been found to be the best binucleating ligand used for such hydrolysis reactions in our studies, use of a base, such as Et 3 N, becomes absolutely necessary for the Zn­(II)-mediated C–S bond hydrolysis reaction to proceed in the present work. In line with this, stirring a mixture of 4a and water in DMF for 7 days (in the absence of Et 3 N) could not yield PhOH, and only the starting material ( 4a ) was recovered (Figure S53) instead of 2 .…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Moreover, Zn­(II) could not mediate the C–S bond cleavage of thiolates in yet another binucleating ligand system, N -Et-HPTB 1– ( N -Et-HPTB 1– is the deprotonated version of N , N , N ′, N ′-tetrakis­[2-(1- ethylbenzimidazolyl)]-2-hydroxy-1,3-diaminopropane) , in one of our previous studies, although Fe­(II) and Co­(II) could mediate the hydrolysis reaction , using the same N -Et-HPTB 1– ligand. Therefore, it becomes quite apparent that Zn­(II) is indeed comparatively much less efficient in mediating the C–S bond cleavage of thiolates, and hence even with the use of the PhBIMP 1– ligand, which, by far, has been found to be the best binucleating ligand used for such hydrolysis reactions in our studies, use of a base, such as Et 3 N, becomes absolutely necessary for the Zn­(II)-mediated C–S bond hydrolysis reaction to proceed in the present work. In line with this, stirring a mixture of 4a and water in DMF for 7 days (in the absence of Et 3 N) could not yield PhOH, and only the starting material ( 4a ) was recovered (Figure S53) instead of 2 .…”
Section: Resultsmentioning
confidence: 67%
“…Here, it may be noted that the role of Et 3 N was examined by us previously and it was found to be nonessential for the Co(II)-and Fe(II)-mediated C−S bond hydrolysis of thiolates using the same PhBIMP 1− ligand, 35,36 although the presence of Et 3 N was found to increase the yield marginally. We have explained in one of our previous reports that upon going from Fe(II) to Zn(II), the effective nuclear charge on the metal center increases, which in turn decreases the pK a of the metalbound water molecule and the nucleophilicity of the metalbound hydroxide ion.…”
Section: Synthesis Ofmentioning
confidence: 69%
See 2 more Smart Citations
“…Interestingly, the reaction systems involving HPhBIMP and either Co(II) or Fe(II) could also desulfurize elemental sulfur (S 8 ) to yield 6a(BF 4 ) 2 and 8a(BF 4 ) 2 in 53% and 22% yields, respectively, while the generation of S It was also found that the catalytic hydrolysis of thiolates was not favorable under acidic conditions, while the use of a base, such as Et 3 N, did not improve the results. Catalytic hydrolysis of a total of 11 substrates (Scheme 8) was explored at RT, 136 and the results (Table 2) showed that the catalysis was comparatively more efficient for aliphatic thiolates (yield of alcohols = 81−90%) than that for the aromatic thiolates (yield of phenols = 31−52%), which, however, was consistent with our previous reports on stoichiometric hydrolysis of thiolates 125 and the reported level of difficulty (alkyl mercaptans < aromatic mercaptans) for removing sulfur in crude oil by the HDS process. 7−9 The identity of the recovered catalyst (6a) was confirmed by unit-cell determination of the single crystals, mass spectrometry, and solution magnetic moment measurement by Evans' method (in comparison with an authentic sample of 6a), while the generation of hydrosulfide (HS − ) during the catalysis was confirmed by the precipitation of insoluble CuS.…”
Section: Consecutive Cleavage Of C−s and S−s Bonds In Disulfidesmentioning
confidence: 99%